Generic and Automated Data Evaluation in Analytical Measurement. (April 2017) - Adam, Martin; Fleischer, Heidi; Thurow, Kerstin
In the past year, automation has become more and more important in the field of elemental and structural chemical analysis to reduce the high degree of manual operation and processing time as well as human errors. Thus, a high number of data points are generated, which requires fast and automated data evaluation. To handle the preprocessed export data from different analytical devices with software from various vendors offering a standardized solution without any programming knowledge should be preferred. In modern laboratories, multiple users will use this software on multiple personal computers with different operating systems (e.g., Windows, Macintosh, Linux). Also, mobile devices such as smartphones and tablets have gained growing importance. The developed software, Project Analytical Data Evaluation (ADE), is implemented as a web application. To transmit the preevaluated data from the device software to the Project ADE, the exported XML report files are detected and the included data are imported into the entities database using the Data Upload software. Different calculation types of a sample within one measurement series (e.g., method validation) are identified using information tags inside the sample name. The results are presented in tables and diagrams on different information levels (general, detailed for one analyte or sample).